Mengungkap Interaksi Profitabilitas dan Kebijakan Hutang Sebagai Penentu Nilai Perusahaan di Sub-Sektor Makanan dan Minuman: Kebijakan Dividen Sebagai Moderasi - Ayu Kusuma Cahyaningsih; Tiya Nurfauziah; Syarif M. Helmi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The food and beverage industry as part of the non-cyclical consumer sector on the Indonesia Stock Exchange has an important role in supporting the national economy due to its stable growth in the face of economic downturn. However, the weakening of the rupiah exchange rate and the increase in VAT rates pose significant challenges, especially related to the cost of importing raw materials and consumer purchasing interest. This study aims to analyze the effect of profitability and debt policy on firm value, as well as the role of dividend policy as a moderating variable in food and beverage sub-sector companies on the IDX for the 2021–2024 period. The research method used is quantitative. Data analysis techniques use descriptive statistics, classical assumption tests, multiple linear regression analysis, MRA tests, and hypothesis tests to see the relationship between variables. The sample used in this study amounted to 96 data with a period of 4 years of research selected through purposive sampling criteria. The results of the study indicate that profitability as measured by ROE has a positive and significant effect on the value of the company's debt policy as measured by DER has a negative and significant effect. In addition, dividend policy is proven to be unable to moderate the relationship between profitability and debt policy on firm value